Integração de bibliotecas científicas de propósito especial em uma plataforma de componentes paralelos - Ferreira, Davi Morais (2010)
The contribution of traditional scienti c libraries shows to be consolidated in the construction of high-performance applications. However, such an artifact of development possesses some limitations in integration, productivity in large-scale applications, and exibility for changes in the context of the problem. On the other hand, the development technology based on components recently proposed a viable alternative for the architecture of High-Performance Computing (HPC) applications, which has provided a means to overcome these challenges. Thus we see that the scienti c libraries and programming orientated at components are complementary techniques in the improvement of the development process of modern HPC applications. Accordingly, this work aims to propose a systematic method for the integration of scienti c libraries on a platform of parallel components, HPE (Hash Programming Environment), to o er additional advantageous aspects for the use of components and scienti c libraries to developers of parallel programs that implement high-performance applications. The purpose of this work goes beyond the construction of a simple encapsulation of the library in a component; it aims to provide the bene ts in integration, productivity in large-scale applications, and the exibility for changes in the context of a problem in the use of scienti c libraries. As a way to illustrate and validate the method, we have incorporated the libraries of linear systems solvers to HPE, electing three signi cant representatives: PETSc, Hypre, e SuperLU.